Surface Treatment of Textiles - Kan, Chi-wai (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Textiles are commonly constituted of natural and synthetic fibers for normal applications. To impart functional or aesthetic effects on the textiles, the surface characteristics in the fiber play an important role. Therefore, surface treatment or modification is a possible way to provide value-added properties to textiles. The textile material/fiber surface can be treated or modified physically and/or chemically to achieve different desired effects. This book will provide an open forum to draw the attention of academic researchers and industrial experts to looking into different aspects of the surface treatment of textiles.